Collaboration of the Analytical Hierarchy Process (AHP) Method with Simple Additive Weighting (SAW) in Determining the Recipients of Direct Cash Assistance (BLT) - Ferina Gunawan; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
At this time the government often to provides social assistance such as cash assistance (BLT) one of them in Menteng sub district, But the implementation of the distribution is still problematic because the implementation of the distribution is still subjective. With this the author utilizes a decision support system using Analytical Hierarchy Process (AHP) method to determine the weight and Simple Additive Weighting (SAW) method for ranking. So the results of the design of this system can assist in selecting and determining BLT recipients so that the distribution is right on target. The result of the collaboration between the AHP method and the SAW method get the ranking results with the highest preference value is 0.65 and the lowest is 0.30